CD38 Multi-Functionality in Oral Squamous Cell Carcinoma: Prognostic Implications, Immune Balance, and Immune Checkpoint - Ding, Zhuang; He, Yijia; Fu, Yong; Zhu, Nisha; Zhao, Mengxiang; Song, Yuxian; Huang, Xiaofeng; Chen, Sheng; Yang, Yan; Zhang, Caihong; Hu, Qingang; Ni, Yanhong; et al. (Frontiers in Oncology, 2021)
Background CD38 belongs to the ribosyl cyclase family and is expressed on various hematological cells and involved in immunosuppression and tumor promotion. Although targeting CD38 antibodies has been approved for treatment of multiple myeloma, the function of CD38 in solid tumor, oral squamous cell carcinoma (OSCC) etc., has not been investigated. Methods This retrospective study included 92 OSCC samples and analyzed the spatial distribution of CD38 by immunohistochemistry (IHC). The values of diagnosis and prognosis of CD38 were evaluated. Additionally, 53 OSCC preoperative peripheral blood samples were used to be analyzed by flow cytometry. Tumor Immune Estimation Resource (TIMER) and cBioPortal databases were used to study CD38 level in various tumors and its correlation with tumor immune microenvironment in head and neck squamous cell carcinoma (HNSCC). Results CD38 ubiquitously presented in tumor cells (TCs), fibroblast-like cells (FLCs), and tumor-infiltrating lymphocytes (TILs). Patients with highly expressed CD38 in TCs (CD38TCs) had higher TNM stage and risk of lymph node metastasis. Upregulation of CD38 in FLCs (CD38FLCs) was significantly associated with poor WPOI. Escalated CD38 in TILs (CD38TILs) led to higher Ki-67 level of tumor cells. Moreover, patients with enhanced CD38TCs were susceptible to postoperative metastasis occurrence, and those with highly expressed CD38TILs independently predicted shorter overall and disease-free survival. Strikingly, patients with highly expressed CD38TILs, but not CD38TCs and CD38FLCs, had significantly lower CD3+CD4+ T cells and higher ratio of CD3−CD16+CD56+NK cells. The imbalance of immune system is attributed to dysregulated immune checkpoint molecules (VISTA, PD-1, LAG-3, CTLA-4, TIGIT, GITR) as well as particular immune cell subsets, which were positively correlated with CD38 expression in HNSCC. Conclusion CD38 is a poor prognostic biomarker for OSCC patients and plays a vital role in governing immune microenvironment and circulating lymphocyte homeostasis. Co-expression between CD38 and immune checkpoint molecules provides new insight into immune checkpoint therapy.